The Playful Path: Analyzing Gamification and Motivation in EFL Grammar Teaching-Learning Process - Gusta, Wienda; Putri, Dwi Megista; Permata, Riyen (JOINT: Journal of Inspirational English Language Teaching, 2024)
The gamification implementation in education is gaining interest as an effective strategy to enhance student engagement and motivation, especially in English as a Foreign Language (EFL) contexts. However, its effect on grammar acquisition is insufficiently researched, raising inquiries regarding its impact on learners’ motivation and grammatical proficiency. This study examines the effectiveness of gamification in EFL grammar training, emphasizing its impact on student motivation and grammatical proficiency. The research used mixed-methods with 45 first-year university students at Universitas Putra Indonesia YPTK Padang, representing diverse competence levels. Data were collected through questionnaires and interviews to investigate students’ opinions of gamified activities and their levels of motivation. A statistical analysis was performed to determine the relationship between gamification and grammatically performance. The results indicated a substantial enhancement in student motivation and engagement with the integration of gamified components into grammar instruction. Participants indicated enhanced satisfaction and a more positive tendency towards grammar learning, resulting in increased grammatical accuracy. These findings highlight the potential of gamification to enhance the engagement and effectiveness of language acquisition. The research offers significant insights for educators aiming to create dynamic and engaging curriculum, revealing how interactive components can enhance grammar instruction and create improved learning results.